Big Data Prediction Framework for Weather Temperature Based on MapReduce Algorithm - Khalid Adam, Ismail Hammad; Jasni, Mohamad Zain; Mazlina, Abdul Majid; Noor Akma, Abu Bakar (IEEE, 2016)
Weather is the most critical for human in many aspects of life. The study and knowledge of how weather Temperature evolves over time in some location or country in the world can be beneficial for several purposes. processing, Collecting and storing of huge amounts of weather data is necessary for accurate prediction of weather. Meteorological departments use different types of sensors such as temperature, humidity etc. to get the data. The sensors volume and velocity of data in each of the sensor make the data processing time consuming and complex. This project aims to build analytical Big Data prediction framework for weather temperature based on MapReduce algorithm.